Carbon Dots Hybrid Nanostructure-based Electrochemical Sensors: Applications in Determining Different Species in a Real Sample - Ferreira, Joao A.; Name, Luccas L.; Lieb, Laura C.; Tiba, Daniel Y.; da Silva, Mariana M.; Oliveira, Aprys C.; Canevari, Thiago C. (Current Nanoscience, 2024)
This overview describes the synthesis, characterization, and application of different carbon dots hybrid nanostructures obtained by chemical interaction between nanomaterials or nanomaterials bonded to another material, i.e. silicon (SiO2/Carbon dots-N), reduced graphene oxide (rGO/Carbon dots), multiwalled carbon nanotubes (MWCNTs/Carbon dots), nano magnetite (Carbon dots/Fe3O4), reduced graphene oxide and gold nanoparticles (rGO/Carbon dots/AuNPs), copper oxide (CuO/Carbon dots), and Carbon dots/Metallic NPs that were employed in the development of electrochemical (bio)sensors. The formation of different carbon dots hybrid nanostructures has been characterized by X-ray diffraction (XRD), Raman and ultraviolet- visible spectroscopy, atomic force microscopy (AFM), high-resolution transmission electron microscopy (HR-TEM), and electrochemical techniques. These carbon dots hybrid nanostructures have been used to modify the surface of glassy carbon and screen-printed electrodes and to determine various analytes, i.e., dopamine, uric acid, paracetamol, ephynefrin, dihydroxybenzenes, pesticides, endocrine disruptors, NADH, and other substances in real samples.
Keywords: real samples